2014
DOI: 10.1179/1743132814y.0000000361
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative embolization of hypervascular spinal tumors: current practice and center experience

Abstract: Preoperative transarterial embolization of hypervascular spinal tumors has been extensively used, and is considered to be a highly effective adjuvant technique in reducing intraoperative blood loss during surgery. Moreover, it has been reported to increase the feasibility and safety of the surgical procedure, leading to better surgical outcomes. We review the English literature in an attempt to identify indications, appropriate timing of embolization in relation to surgery, technical aspects of the procedure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 37 publications
1
26
0
1
Order By: Relevance
“…Moreover, highly vascularized tumors including renal and thyroid carcinoma are associated with a high risk of massive blood loss. In this regard, transarterial embolization has been reported to decrease perioperative bleeding in hypervascular tumors [5,8-10,12,15,16,21]. However, consensus regarding embolization in non-hypervascular spinal metastasis has yet to be achieved [3,8,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, highly vascularized tumors including renal and thyroid carcinoma are associated with a high risk of massive blood loss. In this regard, transarterial embolization has been reported to decrease perioperative bleeding in hypervascular tumors [5,8-10,12,15,16,21]. However, consensus regarding embolization in non-hypervascular spinal metastasis has yet to be achieved [3,8,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors demonstrated that preoperative embolization for spinal tumor is a safe procedure [9,10,12,20] and no complications were observed in their series [9,10,12,16,20]. However, it does carry certain risks for complication (i.e., cerebral infarction, cord ischemia, aortic dissection, and muscle necrosis) and the published rates of complication vary from 1 to 8.5 % [11,[21][22][23].…”
Section: Discussionmentioning
confidence: 92%
“…Preoperative tumor embolization is a standard for surgery of hypervascular spinal tumors. 19 23 Nonetheless, not all sources of intraoperative bleeding can be controlled by means of arterial embolization. Difficulties in accessing the operation field and networks of venous structures and technical problems provide a small residual risk of massive hemorrhage even if the tumor itself is completely excluded from the arterial circulation.…”
Section: Discussionmentioning
confidence: 99%